Pengaruh Program Numpang Nampang RRI Pro 2 (88,4 FM) terhadap Pemenuhan Kebutuhan Informasi Event di Kalangan Mahasiswa - Wahyudi, M. Dwi Rizki; Ismandianto, Ismandianto (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
The Numpang Nampang program is a radio program that is presented in a chat format that discusses light information about achievements, the work of individuals, organizations, schools, campuses and communities, according to the themes and invited speakers. Starting from the S-R (Stimulus-Response), the stimulus in this research is the Numpang Nampang RRI Pro 2 Program (88.4 FM), while the response, namely the action or attitude towards the stimulus given is the fulfillment of the event's information needs after listening to the program. This study used a quantitative approach using a sample of 100 respondents. Data testing was carried out using the SPSS application for Windows with multiple linear regression analysis. Through the F test, a significance value of 0.000 is obtained, which is less than α = 0.05 and Fcount = 86.284, which is greater than Ftable = 2.699. It can be concluded that there is an influence between the Numpang Nampang RRI Pro 2 Program (88.4 FM) on Fulfilling Needs Event Information Among Pekanbaru City Students, The determination test shows the influence of the Numpang Nampang RRI Pro 2 Program (88.4 FM) on Fulfilling Event Information Needs among Pekanbaru City students by 72.9% with a strong level of influence.